The Impact of Natural Resource Abundance on Economic Growth in Nigeria: A Look at History for the Sake of Future - T.A, Mangbon,; S.M., Ojonye, (IJRDO - Journal of Applied Management Science, 2017)
One of the most disturbing characteristics of modern economic growth history is that economics that are well-endowed with natural resources have tended to grow slower than economies not well endowed with natural resources. While economic historians and development economists have been puzzled over the addity of resource-poor countries outperforming the resource-rich ones in their living standards, this study examines the impact of natural resource dependency on economic growth in Nigeria within the framework of autoregressive methodology. Exploiting a time series data for the period 1970 – 2014, the study found the speed of adjustment (1 - ) at which per capita income returns to its steady state equilibrium position to be about 39 percent after it wonders away within two years and that natural resource dependency has not significantly enhance economic growth in Nigeria. Based on this finding, it is recommended that sustainable growth of income per capita can be achieved by initiating appropriate macroeconomic policies that are aimed at improving the efficiency and effectiveness of natural resource exploitation in the economy, and a revision of fiscal and budgeting systems.